Novick Learning Model Design For Conceptual Understanding Ability - Adi Suarman Situmorang; Golda Novatrasio Sauduran; Melinda G. Limbong; Maesy Romaito Purba (LPPM Universitas PGRI Sumatera Barat, 2023)
This study was conducted to see how the improvement of students' conceptual understanding ability taught with the Novick learning model design with a population of all students of the Mathematics Education Study Program, FKIP UHN Medan and the sample was all students who took the mathematics learning outcome evaluation course. With the random sampling technique, two classes were selected as one class experimental group and one class as the control group. The results of the study obtained were that all learning devices designed were declared valid and suitable for use, as seen from the final value of the validator as a whole, which was in the assessment interval of 4.50-5.00 , with the category of